Small Islands and Coral Reef Ichthyofaunas as the Basic Data for the Fisheries Resource Management - Renny Kurnia Hadiaty; MF Rahardjo; Gerald R Allen (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2019)
Indonesia is one of the biggest archipelago country in the world, These islands lined up, stretching from Sabang to Merauke. Some government institutions studied the number of islands in Indonesia. In March 2nd 2017 President of Republic Indonesia issued Keppres No. 6 2017 about 111 numbers of outer islands. Two of the islands belongs to Bengkulu Province, i.e Enggano and Mega islands. Stretching in an east-west direction embracing nearly 18,000 islands, the Indonesian Archipelago features a seemingly endless array of marine habitats. The country is the global leader with regards to area occupied by coral reef, estimated at 51,090 km2. The total number of coral reef fishes around 2600 species. The highest diversity of coral reef fishes with about 1766 species is Papua Barat. The dominant family is Gobiidae with 405 species, Labridae about 200 species and Pomacentridae with about 176 species. The islands in Indonesia have a unique history and inhabit by numbers of endemic fish species, i.e Muna island, Aru islands, and Enggano island. LIPI conducted an expedition in Enggano in 2015, the result indicated some undescribed species there. The new species found in Indonesia since a long time ago, started on 16 century up to now. The research on freshwater fish in Indonesia found 66 new fish species. Until now there are still a lot of unexplore waters in Indonesia, and there are still awaiting undescribe fish species to be named. Fish conservation in the small islands need to be done, as most of them migrate to the sea. Some aphidromous species growth and reproduction in freshwaters but the juvenile migrate downstream towards the sea, spreading at sea, metamorphosis phase they enter upstream migration and settlement in the freshwater. Abstrak Indonesia merupakan negara kepulauan yang terbesar di dunia, pulau-pulau ini berjajar, membentang dari Sabang sampai Merauke. Kajian jumlah pulau di Indonesia telah diteliti oleh beberapa lembaga di negeri ini. Sebagai negara kepulauan, Indonesia seolah-olah merupakan habitat laut yang tak berujung. Terumbu karang negeri ini sekitar 51.090 km2 merupakan yang terluas di dunia. Jumlah total spesies ikan di perairan terumbu karang Indonesia sekitar 2600 spesies. Wilayah tertinggi keragaman jenisnya adalah perairan Papua Barat dengan 1766 spesies. Famili yang terbesar adalah Gobiidae 405 spesies, selanjutnya Labridae 200 species dan Pomacentridae 176 spesies. Banyak pulau mempunyai riwayat unik dan dihuni oleh spesies-spesies endemik, diantaranya Pulau Muna, Pulau di Kepulauan Aru, juga Pulau Enggano. Hasil penelitian LIPI di P. Enggano mengindikasikan adanya beberapa jenis baru ikan. Penemuan spesies baru telah berlangsung lama, sejak penelitian iktiofauna di Indonesia dimulai pada abad 16 sampai saat ini. Hasil penelitian ikan air tawar di perairan Indonesia telah mendapatkan 66 spesies baru, sampai saat ini masih banyak wilayah perairan belum diteliti dan kemungkinan besar ada spesies baru yang menanti diungkap keberadaannya. Konservasi spesies ikan di pulau-pulau kecil perlu dilakukan, mengingat banyak diantara-nya yang beruaya ke laut. Beberapa spesies gobiid bersifat amfidromus, memijah dan menetas di perairan tawar namun anakannya bermigrasi ke laut, mengalami metamorphosis dan kembali lagi ke perairan tawar.